The role of financial literacy in achieving financial inclusion: A theoretical and applied study in Arab Countries for the period (2004-2020) - Hasnia, Douma; Fatima, Sabah; Djihad, Belghazli Zohra (The International tax journal, 2026)
This paper contributes to the study of the role of financial literacy in promoting financial inclusion by examining the relationship between the composite financial inclusion index (IFI) and the literacy rate, and the percentage of the population between the ages of 25 and64 years, which represents the variable of financial literacy and its relationship to financial depth and financial literacy between the sexes of the selected Arab countries during the period from 2013 to 2020. Using a multiple linear regression model according to the method of least squares (OLS) under panel data (panel), based on models of fixed and random effects, and to choose the appropriate model for the study, we conducted the Hausman test. The results of the tests showed a positive relationship between financial inclusion and financial literacy, regardless of gender, as well as a positive relationship with financial depth. A negative relationship was observed with GDP, indicating the contribution of financial literacy in promoting financial inclusion in the studied countries. This requires better financial education.